1956
DOI: 10.2134/agronj1956.00021962004800080012x
|View full text |Cite
|
Sign up to set email alerts
|

A Cytogenetical Analysis of Reactions to Wheat Streak‐mosaic Virus in Certain Agrotricum Hybrids1

Abstract: Synopsis The local lesion type of resistance to wheat streak‐mosaic virus exhibited by an intermediate type Agrotricum (2 n = 56) is conditioned by factors located on one or more chromosomes non‐homologous to common wheat (2n = 42), chromosomes. Therefore, the transfer of this type of resistance from the Agrotricum hybrid to common wheat would appear to be most difficult at least with the particular Agrotricum strain used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1961
1961
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Some of these studies have indicated that WSMV resistance from E. ponticum was recessive at 27 • C. It was incompletely dominant at 22 • C and dominant in field tests (Friebe et al, 1996;Martin, 1978). Other studies have suggested that the WSMV resistance from E. ponticum was controlled by multiple genes (Swarup et al, 1956). OK65C93-8 is a winter wheat breeding line with a high level of WSMV resistance from E. ponticum developed by irradiation (Sebesta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have indicated that WSMV resistance from E. ponticum was recessive at 27 • C. It was incompletely dominant at 22 • C and dominant in field tests (Friebe et al, 1996;Martin, 1978). Other studies have suggested that the WSMV resistance from E. ponticum was controlled by multiple genes (Swarup et al, 1956). OK65C93-8 is a winter wheat breeding line with a high level of WSMV resistance from E. ponticum developed by irradiation (Sebesta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%